Sustainability in Youth: Environmental Considerations in Adolescence and Their Relationship to Pro-environmental Behavior - Balundė, Audra; Perlaviciute, Goda; Truskauskaitė-Kunevičienė, Inga (Frontiers in Psychology, 2020)
Adolescents today face the negative outcomes of climate change, and their pro-environmental behavior is crucial to mitigate these negative outcomes. Yet, we know little about what influences adolescents’ pro-environmental behavior. Research shows that people’s biospheric values and environmental self-identity, elicit personal norms to act environmentally friendly, which can induce a wide range of pro-environmental actions. Yet there is no evidence that these factors can influence pro-environmental behavior of adolescents, because this has only been studied for adults. Given that in adolescence, values, identities and moral structures undergo intense development, the question is whether these factors can motivate adolescents to act pro-environmentally. To address this question, we have conducted three studies with adolescents in Lithuania (Study 1: N = 256; Study 2: N = 349; Study 3: N = 905). We found support that adolescents’ biospheric values and environmental self-identity were associated, via personal norms, with a wide range of pro-environmental behaviors, including recycling, environmentally friendly travelling, purchasing environmentally friendly goods and drinking tap water. Based on theory and the current findings, we suggest directions for policies aimed at promoting pro-environmental behavior of adolescents.